Tertib al-Jam‘ dan al-Naskh dalam Mukhtalif al-Ḥadīth Menurut Sharaf al-Quḍāh: Satu Analisis: The Sequence of al-Jam' and Al-Naskh Methodology in Mukhtalif al-Ḥadīth Solution: Analysis the View of Sharaf al-Quḍāh - Ab Razak, Mohd Solleh; Samsudin, Roshimah (Jurnal Usuluddin, 2021)
The method used by hadith scholars in the issue of contradiction between hadith which is termed as Mukhtalif al-Ḥadīth usually involves three manhaj, namely al-Jam‘, al-Naskh and al-Tarjīḥ. In principle, the scholars of hadith arrange the order by putting al-Jam‘ as the first, then al-Naskh and followed by al-Tarjīḥ. However, a contemporary hadith researcher, Sharaf al-Qudāh, was found to have presented a different order as compared with presented by hadith scholars. Therefore, this article aims to examine the views of Sharaf al-Quḍāh regarding the sequence of manhaj solution of Mukhtalif al-Ḥadīth based on the manhaj of hadith scholars. To implement this purpose, the writer is used library research based on qualitative research through contents analysis in order to record and analysis data. The finding of this research shows that the sequence of al-Hadith methodology which is proposed by Sharaf al-Quḍāh is acceptable among muḥaddithīn even though it is not clearly stated in Muṣṭalaḥ al-Ḥadīth writings. Accordingly, this writing is the way to enhance the understanding in accordance with the sequence of aplication methodology amongs the muhaddithīn in order to eliminate the contradiction between al hadith.